Foliar absorption and field herbicidal studies of atrazine-loaded polymeric nanoparticles - Takeshita, Vanessa (2021)
Nanoparticles loaded with atrazine show weed control efficacy even with lower application doses of the active ingredient. Changes in the mode of action of the herbicide through the nanoformulation are key to understanding the efficiency of post-emergence activity of nanoatrazine. Here, we report the leaf absorption and translocation of nanoatrazine and atrazine employing radiometric techniques and compare their herbicidal effects in greenhouse and field conditions. Compared to the commercial formulation, nanoatrazine showed greater and faster absorption rates in mustard leaves (40% increment in the absorbed herbicide 24 h after application), inducing higher inhibition of photosystem II activity. Assays with fusicoccin-treated leaves indicated that the stomatal uptake of nanoparticles might be involved in the improved activity of nanoatrazine. Nanoencapsulation potentiated the post-emergent herbicidal activity of atrazine and the gain provided by nanoencapsulation was higher in the field compared to greenhouse conditions. Regardless of the dose, nanoatrazine provided two-fold higher weed control in the field compared to commercial atrazine. Thus, the design of this carrier system enables improvements in the performance of the herbicide in the field with less risk of environmental losses of the active ingredients due to faster absorption.